EMPOWERMENT, MOTIVASI, DAN KINERJA: MENELITI DAMPAK FEEDBACK, REWARD DAN PREFERENSI RISIKO - Sutikno, Ana Maya Jayanti (Jurnal Akuntansi Bisnis, 2012)
Research on empowerment has been done previously by Thomas and Velthouses (1990), followed by Spreitzer and developed back by Drake, Wong, and Salter (2007). Research conducted has the aim to determine whether there is causal relationship between feedback, reward and risk preferences with the empowerment that is divided in three dimension are impact, competence, and self-determination. Participants in this study were students of Unika Soegijapranata, Semarang conditioned as an employee with a random sampling. Data analysis techniques used were ANOVA and Partial Least Square (PLS). The result can be seen that participants with feedback condition had an influence on empowerment, empowerment dimensions, while the impact and effect on the motivation and competence motivation has an influence on performance. The conclusion from this study of performance-based reward and risk preferences have no effect on empowerment, and competence dimensions of empowerment that has no effect on motivation.